2007
DOI: 10.1080/15533170701465697
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sputtering Power on the Physical Properties of Cu3N films Formed by DC Magnetron Sputtering

Abstract: Thin films of copper nitride were deposited on glass substrates using dc reactive magnetron sputtering technique by sputtering of copper target under various sputtering powers in the range 30 -140 watt. The influence of sputtering power on the structural, electrical and optical properties was systematically studied. Single phase films of copper nitride were obtained at a sputtering power of 75 watt with electrical resistivity of 5.8 3 10 22 V cm and an optical band gap of 1.84 eV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…It should be emphasized that the values of the index of refraction reported in our present ellipsometric study are clearly much higher than those measured for Cu 3 N with the prism coupling technique [24]. We considered that the values of the refractive index found with the latter technique, surprisingly, around 1.5 at four wavelengths in the NIR region, are notably underestimated, taking into account that the values of the refractive index determined in our study are very consistent with those previously reported in the literature [25], calculated making use of the popular Swanepoel transmission-envelope method.…”
Section: Uv-mir Ellipsometric Analysissupporting
confidence: 87%
“…It should be emphasized that the values of the index of refraction reported in our present ellipsometric study are clearly much higher than those measured for Cu 3 N with the prism coupling technique [24]. We considered that the values of the refractive index found with the latter technique, surprisingly, around 1.5 at four wavelengths in the NIR region, are notably underestimated, taking into account that the values of the refractive index determined in our study are very consistent with those previously reported in the literature [25], calculated making use of the popular Swanepoel transmission-envelope method.…”
Section: Uv-mir Ellipsometric Analysissupporting
confidence: 87%